Association between lifestyle factors and health-related quality of life in breast cancer survivors and in population-based controls after 15 years follow-up - Rima Koiri (2024)
Introduction: Breast cancer is the most prevalent cancer among women globally, including in Germany, where advancements in early detection and treatment have led to increased survival rates. Despite this progress, approximately 90% of long-term breast cancer survivors experience side effects, that negatively impact survivors' HRQoL. Hence, understanding the HRQoL and modifiable factors such as lifestyle factors associated with determining HRQoL is crucial. This thesis investigates the influence of lifestyle factors (physical activity, alcohol consumption, smoking) on HRQoL in long-term breast cancer survivors, and whether these lifestyle factors impact the HRQoL differently in cases and controls. Materials and Methods: A cross-sectional study was conducted based on data from the MARIE project follow-up 3. Two models were created, Model 1 employed multiple linear regression to assess the impact of lifestyle factors on HRQoL among cases. Model 2 employed multiple linear regression with an interaction term, to see whether lifestyle factors impact HRQoL differently between cases and controls. Both the models were adjusted for confounders.
Keywords: Long-term breast canser survivors; age-matched controls; lifestyle factor; health-related quality of life